Ecological risk assessment of heavy metals in the coastal sediment in the South-western Bay of Bengal - Naik, Subrat; Pradhan, Umakanta; Karthikeyan, P.; Bandyopadhyay, Debasmita; Sahoo, Rabindra Kumar; Panda, Uma Sankar; Mishra, Pravakar; Murthy, M. V. Ramana (Frontiers in Marine Science, 2023)
Dynamic coastal waters are often polluted by chemical pollutants, affecting coastal ecosystems. A total of four scientific coastal cruises up to 10 km offshore from the coastline along the Chennai-Puducherry coast during 2019-20 were conducted. This study examined the spatiotemporal distribution of heavy metals (Cr, Cu, Pb, Cd, Ni, Zn, As, Co, Mn) in the coastal sediments using various geochemical indices, including the Geo-accumulation Index (Igeo), Enrichment Factor (EF), Contamination Factor (CF), and Ecological Risk Index (ERI), to understand the impacts, environmental risks, and pollution status in coastal and marine systems. The heavy metal concentrations of Cr, Cu, Pb, Cd, Ni, Zn, As, Co, and Mn in sediments are 16.48-74.70 μg/g, 2.01-3.78 μg/g, 1.37-17.54 μg/g, 0.20-21.76 μg/g, and 5.73-40.53 μg/g, 4.73-53.54 μg/g, 2.09-28.18 μg/g, 1.80-9.02 μg/g, 70.27-346.22 μg/g, respectively. The Igeo results revealed that none of the metals reached up to the contamination level except for Cd and As which showed a slightly contaminated level of the sediment. ERI indicated that coastal sediments are at moderate to high ecological risk from heavy metals. This study will help policymakers make informed decisions for combating or remediating metal pollution to safeguard the coastal environment.